Salicylic acid enhances Staphylococcus aureus extracellular adhesin protein expression - Alvarez, Lucía Paula (2011)
One of the virulence factors required by Staphylococcus aureus at the early stages of infection is Eap, a secreted adhesin that binds many host proteins and is upregulated by the two-component regulatory system saeRS. The S. aureus Newman strain harbors a mutation in saeS that is thought to be responsible for the high level of Eap expression in this strain. This study was designed to ascertain whether salicylic acid (SAL) affects the expression of Eap and the internalization of S. aureus into epithelial cells. The strain Newman treated with SAL exhibited increased levels of eap transcription and protein expression. Furthermore, SAL treatment increased the eap promoter activity. SAL treatment enhanced Eap expression in the Newman and in other S. aureus strains that do not carry the mutation in saeS. Internalization of S. aureus eap and sae mutants into the MAC-T epithelial cells was significantly decreased compared with the wild-type counterparts. In conclusion, we demonstrated that a low concentration of SAL increased S. aureus Eap expression possibly due to enhancement of sae. SAL may create the conditions for S. aureus persistence in the host, not only by decreasing the capsular polysaccharide expression as shown before, but also by enhancing Eap expression.